Research on Simulation of Regenerative Braking System Based on Actual Driving Cycle - Duong, Tuấn Tùng; Huynh, Phước Sơn; Ho, Dương Anh Duy; Ngo, Quang Thành (Journal of Technical Education Science, 2023)
Currently, the regenerative braking system is a system that helps reduce fuel consumption of Hybrid Electic Vehicle (HEV). The braking or decelerating is the process by which the vehicle's inertia energy is converted into electrical energy to recharge the battery. The recovered energy depends on the vehicle's operating conditions on different types of roads. In this study, the author will build the driving cycle on different roads by experiment such as: in the city, highways and intercity roads. That driving cycle is the input signal in the simulation model to study and calculate the parameters of the regenerative braking process as well as the recovered energy and fuel consumption of the Hybrid vehicle. The simulation model was built based on Toyota Cross Hybrid parameters with simulation results shows that the energy recovered in the city road is higher than in the suburban and intercity roads. The vehicle's fuel consumption is from 4.9 to 5.4 [liters / 100km] depending on the road condition.